PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL MENGGUNAKAN ISPRING SUIT 10 UNTUK MENGEMBANGKAN KETRAMPILAN DIGITAL GURU SEKOLAH DASAR DI SDN 1 KUTA LOMBOK TENGAH - Tahir, Muhammad; Sobri, Muhammad; Novitasari, Setiani; Zain Amrullah, Lalu Wira (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
learning media available. Digital skills can foster numerous new innovations, leading to the creation of various engaging types of educational media. Learning media serve as tools to facilitate the delivery of educational content. The development of educational media should not be separated from the contribution of local wisdom in a given area. Therefore, there is a need for awareness to reintroduce local wisdom as a digital-themed educational medium by enhancing digital skills to achieve this goal. Teachers at SD Negeri 1 Kuta are facing difficulties in developing digital skills, particularly in creating learning media based on local wisdom. These challenges are due to the limited dissemination and training related to the creation of local wisdom-based learning media and the development of digital skills. Therefore, training in the creation of local wisdom-based learning media using iSpring Suite 10 is necessary to develop the digital skills of elementary school teachers at SDN 1 Kuta, Central Lombok.